Revision of Amorphophallus Blume ex Decne. Sect. Rhaphiophallus (Schott) Engl. (Araceae) in India - Jaleel, V. Abdul; Sivadasan, M.; Alfarhan, Ahmed H.; Thomas, Jacob; Alatar, A. A. (Bangladesh Journal of Plant Taxonomy, 2011)
The genus Amorphophallus Blume ex Decne. (Araceae), with more than 200 species, is one of the most taxonomically difficult genera of the family, and in fact is one of the moderately understood of all Asian aroid genera. The 11 sections recognised by Engler have been currently reduced to 10, and out of the 10 sections three, viz. Candarum Engl., Conophallus (Schott) Engl. and Rhaphiophallus (Schott) Engl. are represented in India. Rhaphiophallus as recognized now including sect. Synantherias comprises eight species: Amorphophallus bonaccordensis Sivad. & N. Mohanan, A. hohenackeri (Schott) Engl. & Gehrm., A. konkanensis Hett., S. R.Yadav & K. S. Patil, A. longiconnectivus Bogner, A. margaritifer (Roxb.) Kunth, A. mysorensis E. Barnes & C. E. C. Fisch., A. smithsonianus Sivad., and A. sylvaticus (Roxb.) Kunth. Herein A. bhandarensis S. R.Yadav, Kahalkar & Bhuskute is recognized at the new rank of variety, as A. mysorensis var. bhandarensis (S. R. Yadav, Kahalkar & Bhuskute ) Sivad. & Jaleel. The name Amorphophallus sylvaticus (Roxb.) Kunth is lectotypified here. All except A. sylvaticus (also occurring in Sri Lanka) are endemic to India. Keywords: Araceae; Amorphophallus; Rhaphiophallus; India; Endemics. DOI: 10.3329/bjpt.v18i1.7835 Bangladesh J. Plant Taxon. 18(1): 1-26, 2011 (June)